2009
DOI: 10.1128/jb.01333-08
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Macromolecular Organization of CryofixedMyxococcus xanthusBiofilms as Revealed by Electron Microscopic Tomography

Abstract: Despite the fact that most bacteria grow in biofilms in natural and pathogenic ecosystems, very little is known about the ultrastructure of their component cells or about the details of their community architecture. We used high-pressure freezing and freeze-substitution to minimize the artifacts of chemical fixation, sample aggregation, and sample extraction. As a further innovation we have, for the first time in biofilm research, used electron tomography and three-dimensional (3D) visualization to better reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 53 publications
1
76
0
2
Order By: Relevance
“…2(a, b) shows M. xanthus cells surrounded by myxovesicles of 50-100 nm diameter, some of which are apparently broken, while others remain intact. Occasionally mxOMVs appeared to be linked to the cell surface by a tether, as reported elsewhere (Palsdottir et al, 2009), and vesicles could also appear densely stained, implying that mxOMVs are right-side out and filled with cargo (Fig. 2a, b).…”
Section: Microscopy Of Mxomv Productionmentioning
confidence: 63%
See 1 more Smart Citation
“…2(a, b) shows M. xanthus cells surrounded by myxovesicles of 50-100 nm diameter, some of which are apparently broken, while others remain intact. Occasionally mxOMVs appeared to be linked to the cell surface by a tether, as reported elsewhere (Palsdottir et al, 2009), and vesicles could also appear densely stained, implying that mxOMVs are right-side out and filled with cargo (Fig. 2a, b).…”
Section: Microscopy Of Mxomv Productionmentioning
confidence: 63%
“…Images of mxOMVs have been published previously (Kahnt et al, 2010;Palsdottir et al, 2009;Whitworth, 2011); however, no images have yet captured mxOMV production. To visualize mxOMV production, a culture of M. xanthus was embedded in agar, and cross-sections were imaged by electron microscopy.…”
Section: Microscopy Of Mxomv Productionmentioning
confidence: 99%
“…4A) (127). PilQ belongs to a large family of integral outer membrane secretin proteins that are essential for both pilus biogenesis and TFP-mediated motility (93,126 (96).…”
Section: The Secretin Pilq and Its Cognate Lipoprotein Tglmentioning
confidence: 99%
“…In 2009, Palsdottir et al (12) described small (30-to 60-nm) OMVs in the extracellular matrix of M. xanthus biofilm material. Electron tomography revealed that OMVs were tethered to each other and to the outer membrane.…”
mentioning
confidence: 99%